2013
DOI: 10.1038/jp.2013.149
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-modulated orocutaneous stimulation promotes non-nutritive suck development in preterm infants with respiratory distress syndrome or chronic lung disease

Abstract: BackgroundFor the premature infant, extrauterine life is a pathological condition which greatly amplifies the challenges to the brain in establishing functional oromotor behaviors. The extent to which suck can be entrained using a synthetically patterned orocutaneous input to promote its development in preterm infants who manifest chronic lung disease is unknown.ObjectiveTo evaluate the effects of a frequency-modulated orocutaneous pulse train delivered through a pneumatically-charged pacifier capable of enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 37 publications
2
16
1
Order By: Relevance
“…In general newborns in NNS and pre-feeding oral stimulation groups discharged sooner than control group. This findings (although not statistically significant) agree with Fucile et al ( 19 ) and is in contrast to previous studies, which reported that oral stimulation decreased length of hospital stay ( 15 , 20 ). Our study had several power and weakness.…”
Section: Discussionsupporting
confidence: 81%
“…In general newborns in NNS and pre-feeding oral stimulation groups discharged sooner than control group. This findings (although not statistically significant) agree with Fucile et al ( 19 ) and is in contrast to previous studies, which reported that oral stimulation decreased length of hospital stay ( 15 , 20 ). Our study had several power and weakness.…”
Section: Discussionsupporting
confidence: 81%
“…This minimal frequency adaptation is likely due to the reflexive nature of NNS and the health status of our subjects. Previous research by Barlow and colleagues found that healthy preterm infants manifested significantly longer NNS burst structure with different NNS burst formation compared to premature infants with respiratory distress syndrome (22). …”
Section: Discussionmentioning
confidence: 95%
“…The oral phase of swallowing has been well characterized, as have the effects of oral stimulation and non‐nutritive sucking on continuing development of oral skills . The current study suggests that the presence of oral stimulation with either pacifier intervention, or taste intervention may not significantly or acutely modify pharyngo‐esophageal motility, respiration, or impedance characteristics of swallowing.…”
Section: Discussionmentioning
confidence: 73%
“…For example, patterned orocutaneous therapy using a pacifier has been associated with nonnutritive suck development and enhanced feeding performance, 12 in addition to decreased length of hospitalization. 13 Activation of music by infant sucking patterns has been associated with increased feeding rates and earlier achievement of full oral feeding in preterm infants. 14,15 The use of textured pacifiers has been shown to disrupt and reorganize suck central pattern generation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation